Republicanism and the legitimacy of state border controls - Szilárd János Tóth (Ethics & Global Politics, 2023)
ABSTRACTA number of recent articles have invoked the republican ideal of non-domination to justify either open borders, and/or the reduction of states’ discretionary powers to unilaterally determine immigration policy. In this paper, I show that such arguments are one-sided, as they fail to fully account for the deep ambiguity of the very ideal which they invoke. In fact, non-domination lends just as powerful support to maintaining state border controls as it does to dismantling them. There are only two exceptions to the rule. It is well established that promoting non-domination demands, one the one hand, that refugees be admitted, and second, that all migrants have a right to contest decisions concerning their own admission. But aside from these things, the policy implications of the ideal are unclear. In itself, therefore, it is insufficient to justify either open borders, or the reduction of states said discretionary powers. Such arguments will have to rely on other, additional moral criteria.